3D PRINTING OF PHARMACEUTICALS – A POTENTIAL TECHNOLOGY IN DEVELOPING PERSONALIZED MEDICINE - Jose, Preethy Ani; GV, Peter Christoper (Asian Journal of Pharmaceutical Research and Development, 2018)
The 3D PRINTING technology has caught the attention of medical devices industry and pharmaceutical industry due to its applications on various platform in health care industry. Even though this technology exists for a long time it is of public interest highly now due to the approval of 3-D printed tablet and other medical devices and also with the advent of USFDA’s guidance on technical considerations specific to devices using additive manufacturing which encompasses 3-dimensional (3D) printing has triggered many thoughts about this technology which needs to be considered for successful delivery of intended product. This paper presents regulatory agencies expectations, limitations, problems in establishing such setups for production of drug products, advantages, disadvantages, applications, methods and associated risks involved in manufacturing. It also provides the comprehensive review of the current status of research and development on this platform.